Effect of chain elongation on biological properties of the toxin paralysin β-alanyl-tyrosine - Macurkova, Anna; Neubauerova, Tereza; Poncova, Kristyna; Jezek, Rudolf; Lovecka, Petra; Spiwok, Vojtech; Mackova, Martina; Macek, Tomas (Chemical biology & drug design, 2014)
In hemolymph of insect species, compounds with remarkable properties for pharmaceutical industry are present. At the first line, there were found compounds of low molecular mass, less than 1 kDa. One of such compounds, β-alanyl-tyrosine (252 Da), was isolated from larval hemolymph of some species of holometabolous insects (e.g. Neobellieria bullata). Its paralytic activity and antimicrobial properties were described until now. In this study, we present the effect of elongation of β-alanyl-tyrosine by repeating of this motive on the biological and physical properties of prepared analogues. For assessment of antimicrobial properties of these new compounds strains of Gram-positive, Gram-negative bacteria and fungi were used, we also followed the haemolytic activity and toxic effect on human cell culture HepG2. On the base of ECD spectroscopy measurement, subsequent molecular modelling and known secondary structure of original β-alanyl-tyrosine dipeptide, the secondary structures of repeating sequences of β-AY were specified. The repeating structures of β-alanyl-tyrosine show increase in antimicrobial activity; for Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa, minimal inhibitory concentration was decreased from 30 to 15 mM for 2xβ-AY, 0.4 mM for 4xβ-AY and 0.25 mM for 6xβ-AY.
Keywords: dipeptidy; Microbial Sensitivity Tests; Staphylococcus aureus; Humans; Fungi; Dipeptides; houby; mikrobiální testy citlivosti; Anti-Infective Agents; antiinfekční látky; lidé; proliferace buněk; metamorphosis; Hep G2 Cells; sarcophagin; biologické toxiny; buňky Hep G2; Cell Proliferation; solid phase peptide synthesis; aminokyselinové motivy; Toxins, Biological; Amino Acid Motifs; fleshfly; Neobellieria bullata